The Implementation of Problem Based Learning (PBL) Assisted by Video on Momentum and Impuls Material to Improve Students Critical Thinking Abilities - Hilmi Khoirulloh; I Made Astra; Yuliana Rahayu (Jurnal Penelitian Pendidikan IPA, 2024)
Problem-based learning is a student-centered educational method that aims to develop problem-solving, self-directed learning and teamwork also critical thinking abilities of students. This study aims to determine the effectiveness of applying the Problem Based Learning (PBL) model on momentum and impuls material in improving students critical thinking abilities. This research was conducted using the action research method which was divided into four stages and three learning cycles and also a single case study descriptive research with a critical thinking abilities test instrument. The results of the increasing critical thinking abilities test were analyzed using the N-gain test and paired sample t test. The test results showed that there was an increase in students critical thinking abilities with N-gain score is 0.46 and 0.56 in medium criteria and paired t-test results with a significance level of 5% = 0.000 < 0.05 which shows that there is a different level of critical thinking abilities of students before and after the implementation of the PBL. So, based on these results, it can be concluded that the implementation of the video-assisted Problem Based Learning (PBL) model assisted by videos can improve students critical thinking abilities on momentum and impuls material.